Antimicrobial proteins in the response to graphene oxide in Caenorhabditis elegans. Issue 4 (21st April 2017) - Ren, Mingxia; Zhao, Li; Lv, Xiao; Wang, Dayong
Abstract: Upon exposure to environmental engineered nanomaterials (ENMs), animals will activate certain response signals to protect themselves from the toxic effects. However, the underlying molecular mechanisms for this response are still largely unclear. Using in vivo assay system of Caenorhabditis elegans, we here found that antimicrobial proteins of LYS-1, LYS-8, SPP-1, DOD-6, and F55G11.4 were activated by graphene oxide (GO) exposure. These antimicrobial proteins functioned as molecular targets of transcriptional factor DAF-16 in insulin signaling pathway, and acted in intestine to regulate the response to GO. Among these antimicrobial proteins, DOD-6, F55G11.4, and SPP-1 participated in the formation of signaling cascade of DAF-16-DOD-6-SOD-3-F55G11.4/SPP-1 in response to GO exposure by activating the antioxidation system. Different from this, LYS-1 and LYS-8, two lysozymes, mediated TUB-2 signaling and DAF-8-DAF-5 signaling cascade, respectively, to regulate the response to GO exposure. During the regulation of response to GO exposure, LYS-1 and LYS-8 acted synergistically, which could be largely explained by the observed synergistic interaction between TUB-2 and DAF-8. Therefore, our results demonstrate the crucial protection role of antimicrobial proteins for animals in response to environmental ENMs' exposure. The elucidated different signaling cascades mediated by antimicrobial proteins provide important molecular targets for future toxicity assessment and chemical modification of GO.